The working lives of new writing center directors - Caswell, Nicole I., author; Grutsch McKinney, Jackie, author; Jackson, Rebecca, author; Utah State University Press, publisher (Colorado State University. Libraries, 2016)
Longitudinal qualitative studies that looks at the individual professional lives of nine new writing center directors' labor. The authors adopt case study and interview methodologies to examine the labor these directors performed, as well as the labor they ignored, deferred, or sidelined temporarily.--Provided by publisher.
Foreword by Elizabeth H. Boquet -- Preface: On Collaborative Research -- 1. Introduction -- 2. Methods -- 3. Allison -- 4. Anthony -- 5. Darya -- 6. Isatta -- 7. Jennifer -- 8. Joe -- 9. Katerina -- 10. Mandy -- 11. Sara -- 12. Discussion and Conclusion -- Appendix: Participant Matrix.
Keywords: Writing centers -- United States -- Administration -- Case studies; English language -- Rhetoric -- Study and teaching (Higher) -- United States